Tawsiq Abu Hurairah in the Book of Nasa'i Chapter of Zakat - Siti Rahmah; Reza Pahlevi Dalimunthe (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss Abu Hurairah's tawsiq in the book Sunan An-Nasa'i in the chapter of zakat. This research is a type of qualitative research which is a literature study to interpret the hadith sanad text with the hadith takhrij method and the TMT III theory (tashhih, muqaranah, tahlil, tarjih, tahkim). The results and discussion include biographical data, problems found in the hadiths, the sanad scheme and the results of hadith takhrij. This research concludes that looking at the hadiths examined the quality of the hadiths is dhaif because it is marked by the absence of student teacher recognition. The number of hadiths narrated by Abu Hurairah in the zakat chapter of the book Sunan Nasa'i is 35 traditions.